Guanxi or what is the Chinese for relational theory of world politics - Kavalski, Emilian (Oxford University Press, 2018)
The phenomenon of China’s rise has urged some to look for International Relations (IR) theories with ‘Chinese characteristics’. A number of these have been associated with the ‘relational turn’. Yet, attempts to bring the Anglophone and the Sinophone strands of the relational turn have failed to transcend the bifurcating metanarrative of the mainstream. To rectify this trend, the analysis engages the literatures on guanxi, the relational turn, and Chinese IR and develops a normative claim about the underlying relationality of knowledge production in post-Western IR. The contention is: (i) that the criticism of substantialism offered by the Anglophone literature on the relational turn fails to overcome its Eurocentrism; (ii) that by subscribing to the epistemic duality of the West vs. the non-West, the Sinophone literature has aborted the political promise of the concept of guanxi. The study deploys guanxi to amplify the intrinsic relationality both of global life and the realms of IR.